JOURNALISM ETHICS AND ROLE OF INTERFAITH HARMONY FORUM IN SOCIAL MEDIA - Hipolitus Kewuel (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2019)
Abstract: Human need toward information spread throughout history has always been fulfilled professionally within the field of journalism, whether it is paper-based, audio, or audio-visual. Various scientific paths have been established in finding reliable journalist with professional data collection and presentation, objective report, and ethical in attitude. However, at this moment, the journalism construction as though being tore down by the existence of communication media products which facilitate the growth of social media offering violent and vicious new face of journalism for they recruit the journalists without limit. Anyone can be a journalist and anything may serve as news, without censorship, and profession ethic. In short, social media has been accommodating news distribution without journalism principals. Who is in charge to guide or supervise people's work in social media? It could be the government, educational institution, the professional journalists, and the most substantial is the civil society organizations which directly accommodating the society, in particular the social media activists. The Interfaith Harmony Forum is seen as one of the LSM in charge in nurturing social media activists morality. Interfaith Harmony Forum is targeted particularly since the strategic role they hold in handling ethnical and religious issues which prone in triggering disharmony in social media nowadays. This paper is more a critical reflection on the loss of journalism ethics in social media reports.